Reliability Evaluation of Smart Distribution Networks Considering AC and DC Microgrids - Silva, Elson; Rodrigues, Anselmo; Castro, Jose Filho; da Guia Silva, Maria (International Conference on Probabilistic Methods Applied to Power Systems (Online), 2024)
The main objective of this paper is to propose a probabilistic method to evaluate reliability indices in radial power distribution networks considering AC and DC microgrids subject to technical constraints associated with voltage limits and angular frequency. Violations of these constraints are mapped to partial and total load loss events to evaluate reliability indices. These reliability indices were evaluated using the Sequential Monte Carlo Simulation. The tests results showed that the application of DC microgrids caused reduction in SAIFI and SAIDI indices. Furthermore, it can be observed that the relaxation of network constraints causes an underestimation of reliability indices in both AC and DC microgrids.